ANALISIS FRAMING ZONG DANG PAN DAN GERALD M.KOSICKI PADA PEMBERITAAN KETERLIBATAN LUHUT TERHADAP BISNIS PCR (STUDI KASUS PADA CNBCINDONESIA.COM DAN JPNN.COM) - Fitri Anggraini Aini; Hendra Setiawan (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2022)
Online media is a space to get all information for the wider community. Online media provide information about something that happens every day. Online media are electronic media in the form of gadgets, television, print media, online media, and others. Information that is consumed by the wider community can be obtained through online or mass media in the form of current news. This research uses Framing analysis according to Zong Dang Pan and Kosicki. The aims of this study are 1) to describe the differences between the two media. 2) describe the similarities between the two media. 3) describe the syntactic structure, script structure, thematic structure, and rhetorical structure. This study uses a descriptive qualitative approach. The analysis technique in this study is to find sources, read news, listen to the news, analyze news one by one, and record important parts.keywords: online media, news, framing analysis